1993
DOI: 10.1002/bjs.1800800221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foot compression on the velocity and volume of blood flow in the deep veins

Abstract: The A-V Impulse System reduces the incidence of deep vein thrombosis by pneumatically compressing the venae comitantes of the lateral plantar artery, causing an increase in the velocity of blood in the proximal axial veins. Using a duplex scanner the effects of altering the pressure, pulse duration and frequency of foot compression on the velocity and volume of blood flow in the superficial femoral and popliteal veins were quantified. In 20 legs, foot compression of 50, 125 and 200 mmHg significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 4 publications
1
20
1
Order By: Relevance
“…Foot and/or calf compression has been shown to augment popliteal artery blood flow in both normal volunteers and patients with peripheral arterial disease. 19 While it has been hypothesized that the increase in blood flow is a result of a reduction in the arteriovenous pressure gradient, 8,[10][11][12][13]15,16 there are no studies to our knowledge to confirm this hypothesis. Furthermore, previous studies have used duplex ultrasonography to determine the effects of intermittent pneumatic compression on popliteal artery blood flow, although the reproducibility of this method in this arterial segment has not been determined.…”
mentioning
confidence: 57%
“…Foot and/or calf compression has been shown to augment popliteal artery blood flow in both normal volunteers and patients with peripheral arterial disease. 19 While it has been hypothesized that the increase in blood flow is a result of a reduction in the arteriovenous pressure gradient, 8,[10][11][12][13]15,16 there are no studies to our knowledge to confirm this hypothesis. Furthermore, previous studies have used duplex ultrasonography to determine the effects of intermittent pneumatic compression on popliteal artery blood flow, although the reproducibility of this method in this arterial segment has not been determined.…”
mentioning
confidence: 57%
“…Results from four independent randomised clinical trials have shown that mechanical prophylaxis with foot pumps in THR achieved equivalent -if not superior -results compared to chemical management [5,11,13,16], but the tolerance of the device has been a problem for some patients [3,12]. The effective action of the foot pumps depends on various factors, including the frequency and pressure of the impulses and the dependency of the lower extremities [1,4,10]. It is not known whether the efficacy, safety and compliance of the foot pumps are enhanced by the simultaneous use of graduated compression stockings (GCS).…”
Section: Introductionmentioning
confidence: 99%
“…The size, duration, and profile of that augmentation will be dependent on the particular compression system that is used. Changes have been observed in the femoral vein, as a result of calf and thigh compression, 10 -17 and of foot compression; 14 -19 in the popliteal vein due to calf compression, 13,15,16 and foot compression; 13,15,16,18,19 and in the posterior tibial vein after foot compression. 13,19 It is, of course, difficult to measure changes in the popliteal vein with most thigh-length cuffs, just as measurements in the posterior tibial vein would not describe outflow effects when thigh or calf-length garments are used.…”
Section: What Effect Do Intermittent Compression Systems Have On Venomentioning
confidence: 93%